Comportamiento agronómico del cultivo de maíz (Zea mays L.) sembrado en diferentes grados de compactación del suelo y dosis de fósforo en la zona de Baba - García Bustamante, Catherine Gabriela (2020)
Corn is a short cycle plant, whose production is annual, it is part of the Zea genus, family of grasses. Currently 57% of the national corn production is destined for poultry consumption, 6% of balanced feed for other animals, 25% is destined for export from Colombia and for the industry for human consumption 4 %. In many cases Ecuador exports corn-based by-products. During the year of 2017, Ecuador produced around 1.20 million tons of corn on more than 200,000 hectares planted in the country. Compaction increases mechanical resistance to root penetration, decreasing the volume of soil that can be explored, erosion increases phosphorus losses due to surface runoff, which accelerates eutrophication processes. The objective was to evaluate the agronomic behavior of the maize crop planted in different degrees of soil compaction and doses of phosphate fertilizers in the Baba area. The main factors that have an impact on soil compaction is the use of agricultural machinery. We can say that the ideal soil structure is made up of 50% of the soil, 25% of the water space and 25% of the space with air. Soils with a preserved structure have hardly any restrictions due to water deficit and, conversely, when compaction increases to excessive levels, aeration can be affected if humidity is high and, on the other hand, in dry soil conditions, soil resistance can restrict plant growth. Based on the results obtained, the different levels of soil compaction used in corn cultivation influenced the agronomic behavior and crop yield. Being favorable for production, T8 at 100 kg / ha of phosphorus and soil with a low degree of compaction 3. The incorporation of phosphorus P2O5 was positive in corn cultivation, in treatments with a degree of compaction 3. In the case of the variables evaluated as percentage of chlorophyll, fresh and dry weight of the root and foliage, soil moisture, soil compaction, grains per ear, grain-tuff ratio and yield, presented statistical significance with levels of compaction 3 and phosphorus dose. 100 kg / ha.